Ein Gespräch : Joseph Beuys ; Jannis Kounellis ; Anselm Kiefer ; Enzo Cucchi - Burckhardt, Jacqueline (Zürich : Parkett-Verlag, 1988)
Beuys, Joseph ; Kounellis, Jannis ; Kiefer, Anselm ; Cucchi, Enzo ; Ammann, Jean-Christophe
boek